Gender Differences in Work-Family Conflict: Case of Public Officers in East Java in Post Covid-19 - Muhammad Taufiq; Nur Hidayati (Relasi : Jurnal Ekonomi, 2022)
The COVID-19 pandemic has fundamentally reshaped the work-life interface, forcing public sectors to adopt remote and hybrid work models that blur the boundaries between professional and domestic spheres. This study examines the prevalence and gendered dynamics of Work-Family Conflict (WFC) among public officers in East Java, Indonesia, during the post-pandemic transition. Utilizing a quantitative cross-sectional design, data were collected from 179 public officers (117 males and 62 females) through a purposive online survey conducted between January and February 2022. The research employed a reversed-coded Likert scale to measure WFC, where lower scores indicate higher levels of conflict. Results from the Independent Sample T-test reveal that both male (M = 2.44) and female (M = 2.37) officers experience high levels of conflict, with no statistically significant difference in overall intensity (p = 0.540). However, Confirmatory Factor Analysis (CFA) indicates divergent internal manifestations: male officers’ conflict is primarily driven by behavioral constraints and the limitation of family activities (loading = 0.792), while female officers experience significantly higher cognitive spillover, characterized by persistent work-related thoughts during domestic time (loading = 0.734). These findings suggest that while the structural pressures of public service impose a universal burden, the psychological experience of conflict remains gendered. This study highlights the urgent need for nuanced organizational policies, such as "the right to disconnect" and enhanced schedule autonomy, to mitigate long-term burnout and sustain public service efficiency in the "new normal" era.